Brownian motion simulation of vesicle actin tail formation - Oleinick, A. I. (ХНУРЭ, 2009)
The mathematical model of actin tail formation at the surface of a spherical vesicle is proposed in this article. The simulation of the protein diffusion process, which is complicated by the formation of a protein cluster at the vesicle surface leading to the development of an actin tail, was performed using the Brownian motion approach. Two relevant mechanisms of tail growth are considered and discussed.
Keywords: vesicle; brownian motion; protein diffusion; clusterisation